Peranan Konsep Nilai-nilai Matematika dalam Internalisasi Insan Kamil - 'Azizah, Nilatul; Fitriya, Ita (Journal Intellectual Sufism Research (JISR), 2021)
The lack of knowledge and understanding of human beings to the values implied in mathematics that causes mathematics is considered as a lesson that is very contrary to the concept of religion, especially the field of Sufism when in fact mathematics is a means provided by Allah SWT to facilitate people to carry out the task of servitude and the task of the caliphate to the level of insan kamil. This research uses a qualitative approach. Literature review was used to obtain research data. The results of this study state that the concept of mathematical values in the internalization of insan kamil is to encourage humans to develop problem solving skills, communication skills, and reasoning skills to face every situation and problem in life. This discussion also presented that mathematics in addition to teaching to think and reason but also teach honest, humble, not arrogant, sincere, iffah, consistent and systematic attitude. This is a reflection of insan kamil.